(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
In recent years, plant-based proteins have garnered considerable attention from researchers and practitioners due to their lack of allergenicity, alignment with diverse consumer dietary preferences, and contributions to sustainability issues. The article characterizes the features of the foaming process in food systems and traditional foaming agents. The experience of scientists in utilizing plant-based proteins is analyzed, with their functional properties as foaming agents in food systems examined, emphasizing traditional sources (soy, peas, chickpeas, wheat) and alternative raw materials—aquafaba. Aquafaba, a viscous liquid obtained during the cooking of legumes, aligns with sustainability principles in its production and focuses the attention of theorists and practitioners owing to its ability to replicate the functional properties of egg whites. The influence of extraction, protein modification, and optimization of aquafaba’s foaming capacity depending on preparation conditions is considered. The overall chemical composition of chickpea aquafaba under typical hydrothermal processing parameters, which determines its surface-active properties, has been investigated. The dependence of foaming capacity and foam stability in food systems based on chickpea aquafaba on dry matter content, pH, and the presence of foam structure stabilizers has been studied. The feasibility and appropriateness of using chickpea aquafaba as an effective foaming agent in food products have been demonstrated. The obtained results enabled the development of a model technological scheme for producing food products with a foam structure based on chickpea aquafaba.